UJI INVIVO AKTIVITAS DIURETIKA EKSTRAK ETANOL 70% DAUN UNGU (Graptophyllum pictum (L) Griff) PADA MENCIT PUTIH JANTAN GALUR WISTAR - Recta Olivia Umboro; Dedent Eka Bimmaharyanto; Fitri Apriliany; Iva Rinia Dewi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Traditionally, daun ungu plant (Graptophyllum pictum (L) Griff) has been known to have pharmacological effects that can help with a variety of health issues. This plant’s flavonoid compounds content is thought to have diuretic activity in this plant is believed to have activity. The purpose of this study is to determine the diuretic activity and optimal dose of etanol extract of 70% daun ungu administered orally to male white mice. This is an experimental study with a completely randomized design (CRD) that includes 1 negative control group (Na.CMC 0.5%), 1 positive control group (furosemide 40 mg) and 3 test groups of 70% daun ungu ethanol extract doses of 10 mg/kg BW, 25 mg/kg BW and 40 mg/kg BW with urine volume test parameters. One-way ANOVA and Kruskal-Wallis statistical test were used to analyze the data. The results showed that one-way ANOVA revealed a P < 0.05 (0.012), and P ≤ 0.05 (0.051) for the Kruskal-Wallis test. It can be concluded that 70% daun ungu etahanol exctract has effective diuretics, with an optimal dose